DEMOKRASI DAN KEBIJAKAN PUBLIK: MENGKRITISI POPULISME - Datu Hendrawan (Arete, 2019)
Democracyisbasicallyasystemthatplacesthepeople(demos)asthesu-preme ruler as well as the main power in government. This paper intends to crit-icize the phenomenon of populism that occurs in democracy. The right populismmovement poses a threat to a democratic rule of law because of its power to sup-pressparliaments,dictatethegovernment,intimidatethecourtsandthepolice.In discourse theory and deliberative democracy, Habermas suggests maximizingpublic use of reason as a basis for determining public policy.The communicative ratio that is distinguished from the strategic ratio should be the spirit that underliesthe determination of public policy in a democratic rule of law. In communicative action the intention to be achieved is an intersubjective understanding.Meanwhile, populist movements carry out strategic communication which is often manipulative.